Question
upstudy study bank question image url

QUESTION 4 4.1 Solve for \( x \) : 4.1.1 \( x(x-1)=0 \) 4.1.2 \( 2 x^{2}-4 x-5=0 \) (correct to TWO decimal places) \( 4.13 \quad 5^{\prime}=\frac{1}{125} \) \( 4.14(x-3)(2-x)>0 \) 4.2 Given \( f(x)=x+1 \) and \( g(x)=\frac{-4}{x-3} \) 4.2.1 For which values of \( x \) will \( g(x) \) be undefined? 4.2.2 Solve for \( x \) if \( f(x)=g(x) \)

Ask by Rojas Park. in South Africa
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Solve the equations and inequality as follows: 1. \( x(x-1)=0 \) has solutions \( x=0 \) and \( x=1 \). 2. \( 2x^{2}-4x-5=0 \) has solutions \( x \approx 2.56 \) and \( x \approx -0.56 \). 3. \( 5^{x}=\frac{1}{125} \) has solution \( x=-3 \). 4. \( (x-3)(2-x)>0 \) is true for \( 2 < x < 3 \). For the functions: 1. \( g(x) \) is undefined when \( x = 3 \). 2. \( f(x)=g(x) \) when \( x = 1 \).

Solution

Solve the equation \( x(x-1)=0 \). Solve the quadratic equation by following steps: - step0: Solve by factoring: \(x\left(x-1\right)=0\) - step1: Separate into possible cases: \(\begin{align}&x-1=0\\&x=0\end{align}\) - step2: Solve the equation: \(\begin{align}&x=1\\&x=0\end{align}\) - step3: Rewrite: \(x_{1}=0,x_{2}=1\) Solve the equation \( 2x^{2}-4x-5=0 \). Solve the quadratic equation by following steps: - step0: Solve using the quadratic formula: \(2x^{2}-4x-5=0\) - step1: Solve using the quadratic formula: \(x=\frac{4\pm \sqrt{\left(-4\right)^{2}-4\times 2\left(-5\right)}}{2\times 2}\) - step2: Simplify the expression: \(x=\frac{4\pm \sqrt{\left(-4\right)^{2}-4\times 2\left(-5\right)}}{4}\) - step3: Simplify the expression: \(x=\frac{4\pm \sqrt{56}}{4}\) - step4: Simplify the expression: \(x=\frac{4\pm 2\sqrt{14}}{4}\) - step5: Separate into possible cases: \(\begin{align}&x=\frac{4+2\sqrt{14}}{4}\\&x=\frac{4-2\sqrt{14}}{4}\end{align}\) - step6: Simplify the expression: \(\begin{align}&x=\frac{2+\sqrt{14}}{2}\\&x=\frac{4-2\sqrt{14}}{4}\end{align}\) - step7: Simplify the expression: \(\begin{align}&x=\frac{2+\sqrt{14}}{2}\\&x=\frac{2-\sqrt{14}}{2}\end{align}\) - step8: Rewrite: \(x_{1}=\frac{2-\sqrt{14}}{2},x_{2}=\frac{2+\sqrt{14}}{2}\) Solve the equation \( 5^{x}=\frac{1}{125} \). Solve the equation by following steps: - step0: Solve for \(x\): \(5^{x}=\frac{1}{125}\) - step1: Rewrite in exponential form: \(5^{x}=5^{-3}\) - step2: Set the exponents equal: \(x=-3\) The inequality \( (x-3)(2-x)>0 \) cannot be solved using the provided method. Given \( f(x)=x+1 \) and \( g(x)=\frac{-4}{x-3} \): 1. For which values of \( x \) will \( g(x) \) be undefined? \( g(x) \) will be undefined when the denominator \( x-3 \) is equal to zero. Therefore, \( g(x) \) will be undefined when \( x = 3 \). 2. Solve for \( x \) if \( f(x)=g(x) \): \( f(x) = g(x) \) implies \( x+1 = \frac{-4}{x-3} \). To solve for \( x \), we can cross multiply and solve the resulting equation. Solve the equation by following steps: - step0: Solve for \(x\): \(x+1=\frac{-4}{x-3}\) - step1: Find the domain: \(x+1=\frac{-4}{x-3},x\neq 3\) - step2: Rewrite the fraction: \(x+1=-\frac{4}{x-3}\) - step3: Multiply both sides of the equation by LCD: \(\left(x+1\right)\left(x-3\right)=-\frac{4}{x-3}\times \left(x-3\right)\) - step4: Simplify the equation: \(x^{2}-2x-3=-4\) - step5: Move the expression to the left side: \(x^{2}-2x-3-\left(-4\right)=0\) - step6: Subtract the numbers: \(x^{2}-2x+1=0\) - step7: Factor the expression: \(\left(x-1\right)^{2}=0\) - step8: Simplify the expression: \(x-1=0\) - step9: Move the constant to the right side: \(x=0+1\) - step10: Remove 0: \(x=1\) - step11: Check if the solution is in the defined range: \(x=1,x\neq 3\) - step12: Find the intersection: \(x=1\) Therefore, the solution to the equation \( f(x)=g(x) \) is \( x = 1 \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To solve the equation \( x(x-1) = 0 \), we find the roots by setting each factor equal to zero. Thus, \( x = 0 \) or \( x - 1 = 0 \), leading to \( x = 1 \). For the quadratic \( 2x^2 - 4x - 5 = 0 \), we can use the quadratic formula \( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \). Plugging in \( a = 2, b = -4, c = -5 \), we calculate the discriminant and find the relevant roots, yielding two solutions: approximately \( x = 4.17 \) and \( x = -0.60 \). When determining when \( g(x) = \frac{-4}{x-3} \) is undefined, we see that it’s undefined for any \( x \) that makes the denominator zero. This occurs when \( x = 3 \). To find where \( f(x) = g(x) \), set \( x + 1 = \frac{-4}{x - 3} \). After cross-multiplying and simplifying, you can solve for \( x \) to clarify the relationship between the two functions!

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy